Differentiated and Compatible: conservation in the context of a recovered traditional architecture and urbanism - Semes, Steven (DISEGNARECON, 2009)
Since the adoption of the Venice Charter in 1964, many conservation programs and policies have assumed that new construction in historic settings—and contemporary architecture generally—would continue to reflect what was seen at the time as an irrevocable difference between present-day and historic conceptions of architectural style. Implicit in the Charter’s call for new additions to historic sites to “bear a contemporary stamp,” was a permanent formal contrast between “contemporary” architecture and preexisting traditional work. Such a clear stylistic difference would allow an unequivocal identification of the new addition as distinct from the historic fabric, avoiding any risk of “falsification.” This assumption, restated even more explicitly in some of the Charters and standards enacted subsequently, underlies virtually all conservation and planning practice today.But the identification of “contemporary” architecture with a particular stylistic stance is no longer possible. The production of current designers displays a diversity of appearance and a plurality of aims, from informed exercises in traditional formal languages to seemingly unprecedented configurations that dramatize their striking contrast with historic models. In these circumstances, a presumption in favor of any single design approach as an instrument of conservation policy seems arbitrary at best. Imposing a stylistic preference in opposition to historic typologies and formal languages can prove destructive of the character that makes historic monuments and districts valuable in the first place. In response to increasing public dissatisfaction with the dissonant character of much new construction in historic contexts, architects, preservationists, and urban designers are re-examining the logic of continuity rather than contrast between new construction and historic settings. In light of these developments, policies and practice in conservation must be adjusted accordingly. How might we re-frame the notion of making new construction in historic settings both “differentiated” and “compatible” (as the U.S. Secretary of the Interior’s Standards for Rehabilitation require) if we may no longer depend on stylistic distinction alone to make the difference discernible? What would be the consequence of abandoning explicit difference between new and old altogether? Does the concept of “falsification” have any meaning in a traditional building culture? We can construct a more capacious theory of architectural conservation by re-examining historical practice, avoiding on one hand a too-familiar appropriation of historic fabric for our own purposes and, on the other hand, a too-distanced assumption of difference that decontextualizes valued monuments and urban districts.